Changing Patterns of Son Preference and Fertility in Pakistan - Rashid Javed; Mazhar Mughal (ZBW - Leibniz Information Centre for Economics, 2022)
Using data from two representative Demographic and Health Surveys, we examine the change in son preference over the past three decades and its effects on Pakistani women's fertility. We analyse a number of indicators and employ different empirical methods to come up with strong and persistent evidence for both the revealed and stated preference for sons. This disproportionate preference for boys is visible in increasing desired sex ratio and worsening sex ratio at last birth. Reliance over differential birth-stopping has significantly increased over time as couples are more likely to stop childbearing once the desired number of boys is achieved.
Keywords: D13; J13; O15; C13; Z13; 330; Son preference; Fertility; parity progression; Pakistan